International Handbook on Clinical Tax Education - Lawton, Amy (OBserving Law, 2023)
While tax clinics have existed in the US since the 1970s, they are now being established throughout the world, with recent clinical developments in Australia, the UK and Ireland in particular. Of interest to higher education professionals, the tax profession and policymakers, this practical handbook explores the benefits that a clinical tax education can have and equips readers with the tools needed to start a clinical tax project. It investigates the ways in which tax clinics can both educate and remedy tax positions for local communities. It also explores the higher education setting, in which community tax projects rely on students for their success, offering them the benefits of an alternative learning environment in tax and experience in tax while studying. Beyond identifying the practical benefits, this handbook uses learning from tax clinics to uncover the burdens and impacts of tax policy on more marginalised taxpayers, and how policymakers can tailor tax systems to overcome them.